KEEFEKTIFAN PELAKSANAAN PENANGGULANGAN BENCANA DI KABUPATEN ACEH BARAT - Budi Handoyo, Eddy Purnama, M. Saleh. (Jurnal Ilmu Hukum, 2014)
Abstract: Article 4 of West Aceh Qanun No.13 of 2011 about Disaster Management says that the implementation of disaster management aims to provide protection to the public from the threat of disaster, aligning the legislation that already exists, ensure the implementation of disaster management in a planned, integrated, coordinated, and comprehensive, appreciate the local culture, building and public participation. However, in practice the function structure, substance and legal culture in disaster management has not been effective because it is still faced with many obstacles that affect the effectiveness.The implementation of disaster management in Aceh Barat District have not been fully implemented yet effective considering the functioning of the three elements of the legal system became a major element of disaster management.In fact, if all three elements of a functioning legal system with another implementation of disaster management can be effective as effective as can be seen in the alignment of the substance elements Qanun No.13 of 2012 on the disaster management with other legislation.Effective functioning legal culture provide an understanding of the legal community as integration through community participation and socialization legislation implemented through institutional legal authorities.Factors which become obstacles in the disaster relief efforts in Aceh Barat District include inadequate institutional performance and disaster management officials, the low awareness of disaster risk and low understanding of both the law and public administration officials to the disaster rules. Keywords: Effectiveness and Disaster Management. Abstract: Pasal 4 Qanun Kabupaten Aceh Barat Nomor 13 Tahun 2011 Tentang Penanggulangan Bencana menyebutkan bahwa penyelenggaraan penanggulangan bencana bertujuan memberikan perlindungan kepada masyarakat dari ancaman bencana, menyelaraskan peraturan perundang-undangan yang sudah ada, menjamin terselenggaranya penanggulangan bencana secara terencana, terpadu, terkoordinasi, dan menyeluruh, menghargai budaya lokal, membangun partisipasi dan kemitraan publik. Namun demikian, falam pelaksanaannya fungsi struktur, substansi dan budaya hukum dalam penanggulangan bencana belum berjalan efektif karena masih berhadapan dengan berbagai kendala yang mempengaruhi keefektifan tersebut. Pelaksanaan penanggulangan bencana di Kabupaten Aceh Barat belum sepenuhnya berjalan efektif mengingat belum berfungsinya ketiga unsur sistem hukum yang menjadi unsur utama penanggulangan bencana. Padahal apabila ketiga unsur sistem hukum berfungsi satu dengan yang lain pelaksanaan penanggulangan bencana dapat berjalan efektif seperti efektifnya unsur- substansi dapat dilihat penyelarasan Qanun Nomor 13 Tahun 2012 Tentang penanggulangan bencana tersebut dengan peraturan perundang-undangan lainnya. Efektifnya fungsi budaya hukum memberikan pemahaman hukum terhadap masyarakat secara integrasi melalui partisipasi masyarakat dan sosialisasi perundang-undangan yang dilaksanakan melalui kelembagaan hukum yang berwenang. Faktor yang menjadi kendala dalam upaya penanggulangan bencana di Kabupaten Aceh Barat antara lain belum memadainya kinerja aparat dan kelembagaan penanggulangan bencana, masih rendahnya kesadaran terhadap risiko bencana dan masih rendahnya pemahaman hukum baik itu para pejabat pemerintahan dan masyarakat terhadap aturan-aturan kebencanaan. Kata Kunci : Efektifitas dan Penanggulangan Bencana.